A development of d'Panorama Leisure Services web-based system / Mohd Hafzan Mohamad Dahlan - Mohamad Dahlan, Mohd Hafzan (2002)
d'Panorama Leisure Services web-based system that has two sections. The first is for tourist to view all the interesting place in Malaysia that are divided into 14 states in Malaysia. It also includes tour packages that are offered by d'Panorama Leisure Services.